CONTEMPORARY MODALITIES AND ADVANCED TECHNOLOGIAL APPROASHES IN THE COMPREHEVSIVE MANAGEMENT OF PERIODONTITS (World Bulletin of Public Health, 2026)
The article is devoted to the study of modern methods of treatment of inflammatory periodontal diseases. Inflammatory periodontal diseases are a modern problem in dentistry. Periodontitis is a complex nosological unit among periodontal diseases. The article describes the most frequently used and modern methods and means of treatment of periodontal diseases, as well as the use of LED technologies and ozone therapy for the treatment of inflammatory periodontal diseases. The article presents the modern aspects of conservative treatment of inflammatory periodontal diseases using ultrasound devices, including the apparatus "Vector", antibacterial and phytopreparations. They can be recommended for various forms of pathology or accompany other types of treatment (orthopedic and surgical). According to experts from the world health organization, people aged 35 to 50 years have a periodontal disease rate of 69-98%. Numerous and longterm studies of domestic and foreign authors have proved that the leading etiological factor in the development of periodontal tissue diseases are periodontal pathogenic bacteria. Most of the periodontal pathogenic bacteria are represented by anaerobes, which are highly adhesive, invasive and toxic. Effective treatment of patients with infectious and inflammatory periodontal diseases, as a rule, includes medicinal effects on periodontal pathogenic bacteria as the main etiological factor in the development of gingivitis and periodontitis by local and general use of antibiotics.